2017
DOI: 10.1001/jamasurg.2016.5674
|View full text |Cite
|
Sign up to set email alerts
|

A Framework to Improve Surgeon Communication in High-Stakes Surgical Decisions

Abstract: Importance Although many older adults prefer to avoid burdensome interventions with limited ability to preserve their functional status, aggressive treatments, including surgery, are common near the end of life. Shared decision making is critical to achieve value-concordant treatment decisions and minimize unwanted care. However, communication in the acute inpatient setting is challenging. Objective To evaluate the proof of concept of an intervention to teach surgeons to use the Best Case/Worst Case framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
158
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(159 citation statements)
references
References 44 publications
1
158
0
Order By: Relevance
“…9,13,15,18 A graphic and detailed description of the tool is available in the initial publications. 11,18 The framework is based on a foundation of shared decision-making that is useful in situations in which uncertainty surrounds outcomes and the best choice requires an understanding of the patient's values. 24 The tool aims to help surgeons provide information about treatment options in a way that contextualizes surgical decisions into a larger personal framework for patients.…”
Section: Best Case/worst Case Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…9,13,15,18 A graphic and detailed description of the tool is available in the initial publications. 11,18 The framework is based on a foundation of shared decision-making that is useful in situations in which uncertainty surrounds outcomes and the best choice requires an understanding of the patient's values. 24 The tool aims to help surgeons provide information about treatment options in a way that contextualizes surgical decisions into a larger personal framework for patients.…”
Section: Best Case/worst Case Frameworkmentioning
confidence: 99%
“…10 Often, surgeons frame discussions within the structure of informed consent, which emphasizes the risks of operative intervention and the likelihood of death without surgery. 11 This approach does not convey information in relation to a patients' values or about what it may be like to experience undesirable outcomes and how these may affect quality of life, need for additional treatment and functional status. 12 In addition, options may be framed as a choice between certain death with a nonoperative palliative approach versus a surgical intervention carrying high risk for death and complications; within this framework, many patients hope that they are within the group that survives surgical intervention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the increased risks of intervention in the presence of frailty, shared decision‐making must be adopted to align the person's goals with the choice of surgical interventions. The use of the Best Case/Worst Case framework can promote such shared decision‐making and help surgeons structure treatment conversations to obtain the best outcome for the person and their family …”
Section: Can Frailty Measurement Be Used To Identify a High‐risk Groumentioning
confidence: 99%
“…Decisions related to serious acute surgical problems in elderly, frail patients need to consider their values and establish goals of management. Evaluation of a 2‐h training session for surgeons to use the best case/worst case communication framework showed that experienced surgeons could improve their communication beyond discussion about the clinical problem, the surgical procedure and its complications . Following specific training, surgeons were able to involve patients and families in deliberate dialogue about choice of treatments and likely trajectories including functional decline.…”
Section: Communication With Patientsmentioning
confidence: 99%